Pelatihan Administrasi dan Pengorganisasian UKS SDN Codo 02 Kecamatan Wajak Kabupaten Malang - Muhammad Dwi Yanto Putro; Onyka Abdillah (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The School Health Unit (UKS) is an institution within the school environment that aims to improve student health and encourage healthy lifestyles. The implementation of UKS in schools certainly requires clear and structured administration and organization so that it can run well and provide optimal benefits. Based on the results of field observations, it is known that the administration and organization of the UKS at SDN Codo 2, Wajak District, is still not good. This can be seen from the absence of an organizational structure and picket structure as well as administrative books regarding UKS operations. Considering these facts, KKN students in Codo Village are planning a program for administration and organization of the School Health Unit at SDN CODO 2, Wajak District, Kab. Poor. The steps in implementing the administration and organizing UKS program at SDN Codo 2, Wajak sub-district are as follows: (1) observation at SDN Codo 2, Wajak sub-district, Malang Regency; (2) planning improvements and development with the UKS management; (3) planning the UKS administration management mechanism which will be carried out together with the administrators; (4) conducting UKS administration training for minor doctors; and (5) organizing small doctors. The results of the implementation of administrative programs/activities and the organization of UKS SDN Codo 2, Wajak District, Malang Regency, are very satisfying because 90% of the expected results have been achieved.